Essentials of functional endoscopic sinus surgery - Stammberger, Heinz; Hawke, Michael (Mosby, 1993)
This book follows the same general outline as \"Functional Endoscopic Sinus Surgery\" the author\'s previous book covering the same subject. However, chapters have been deleted on the history of nasal endoscopy, special problems in endoscopic surgery and documentation. In addition, the chapter on radiology has been condensed. What remains is the essential information regarding basic principles, anatomy, diagnosis, indications, technique, post-operative care, results and complications.
Keywords: Otorhinolaryngologic Diseases; chirurgie nosu; Nasal Surgical Procedures; otorinolaryngologické nemoci